Development of an Interactive Animation-Based Learning Media Using Central Kalimantan Folktales to Improve Primary School Students’ Literacy and Numeracy Skills - Bulkani Bulkani; Chandra Anugrah Putra; Andi Riswandi Buana Putra; Muhammad Andi Setiawan (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Background: The low level of literacy and numeracy among primary school students in Indonesia highlights the need for contextual and engaging learning media that reflect local culture. Conventional teaching methods often fail to capture students’ interest and do not integrate local wisdom effectively. Aim: This research aims to develop and test an interactive animation-based learning media using Central Kalimantan folktales to enhance students’ literacy and numeracy skills in primary education. Method: The study employs a research and development (R&D) approach by designing, validating, and testing a digital prototype that combines animation, narration, and interactivity. Expert validation was conducted to refine the prototype, followed by pilot testing in selected partner schools in Central Kalimantan. Data were collected through observations, questionnaires, and learning assessments, and analyzed descriptively to evaluate the media’s effectiveness in improving learning outcomes. Results and Discussion: The results indicate that the interactive animation media successfully increased students’ engagement and motivation, leading to higher literacy and numeracy achievement compared to traditional learning tools. Teachers reported that the integration of local folktales provided meaningful and enjoyable learning experiences while reinforcing students’ cultural identity. The discussion emphasizes the potential of culturally grounded digital media to support the thematic learning approach in the Merdeka Curriculum and contribute to the preservation of local culture. Conclusion: The research concludes that the developed interactive animation learning media based on Central Kalimantan folktales is effective in enhancing primary school students’ literacy and numeracy skills. It also demonstrates significant potential for large-scale implementation, commercialization, and collaboration with the creative industry, reaching Technology Readiness Level 5 as a foundation for sustainable dissemination.